Penguatan Manajemen Keuangan pada Kelompok Usaha Bersama (KUBE) Berkat Ilahi Desa Pulantani - Muhammad Bahit; Syahrial Shaddiq; Monika Handayani; Harry Pratama Yunus; Ihya Ihya; Muhammad Fauzan Ahsani; Muhammad Rivaldi Akbar (KREATIF: Jurnal Pengabdian Masyarakat Nusantara, 2026)
This Community Partnership Program (PKM) aims to improve the financial management capacity of the Berkat Ilahi Joint Business Group (KUBE), a purun weaving artisan group in Pulantani Village, Hulu Sungai Utara Regency, South Kalimantan. The partners' main challenges were the lack of structured financial records and inaccuracies in calculating the cost of goods sold (COGS). To address these challenges, a web-based accounting information system was developed to facilitate financial recording, COGS calculations, and budget planning. Implementation methods included outreach, workshops, mentoring, and evaluation. Results showed that more than 85% of KUBE members were able to independently manage COGS reports, financial reports, and digital marketing content. The implementation of this program not only increased transparency and accountability in financial management but also opened broader market access through digital platforms. This program is expected to support the sustainability of the purun weaving business and strengthen the local economy based on empowerment and innovation